2009
DOI: 10.1007/s13157-009-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fire on Riparian Forests Along a Free-Flowing Dryland River

Abstract: Riparian fire studies in the American Southwest have focused on flow-regulated rivers and typically show increase in introduced Tamarix, a species with high resprout capacity, and declines in Populus. Effects of fire, however, can vary with environmental setting. We examined riparian fire along the free-flowing Upper San Pedro River (Arizona) by making temporal comparisons supplemented by spatial contrasts between burned and unburned sites. Pre-fire, Populus fremontii and Salix gooddingii were dominant species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…Fire has also influenced the species composition, structure, and environmental conditions of the riparian and aquatic communities associated with stream networks that drain these landscapes (Gom and Rood 1999;Everett and others 2003;Skinner 2003;Reeves and others 2006;Petitt and Naiman 2007;Stromberg and Rychener 2010). Research on riparian fire frequency and severity has primarily been conducted in forests of the Pacific Northwest (see text box on fire histories in riparian areas).…”
Section: Firementioning
confidence: 99%
“…Fire has also influenced the species composition, structure, and environmental conditions of the riparian and aquatic communities associated with stream networks that drain these landscapes (Gom and Rood 1999;Everett and others 2003;Skinner 2003;Reeves and others 2006;Petitt and Naiman 2007;Stromberg and Rychener 2010). Research on riparian fire frequency and severity has primarily been conducted in forests of the Pacific Northwest (see text box on fire histories in riparian areas).…”
Section: Firementioning
confidence: 99%
“…Based on our results, reduction of willow cover and promotion of grassland cover by fire are the most likely candidates. We found both habitat covariates useful for modeling whether a habitat patch would be mixed (both GWWA and BWWA) or pure GWWA and both willow cover (negatively) (Lee et al 2005, Stromberg andRychener 2010) and grassland cover (positively) (Higgins et al 1989, Telfer 2000 are affected by fire. Our results are consistent with Klaus and Buehler (2001) and Confer et al (2003) who demonstrated a negative relationship between canopy cover and GWWA nest site selection and fledging success respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the short-term, riparian water use could increase by the abundance of sprouting shoots [8]. In the long-term, however, changes in forest composition by shifts in tree-age structure may reduce the forest leaf area compared to a pre-fire condition, ultimately decreasing the ET rates [72]. …”
Section: Impact Of Wildfire On Water Usementioning
confidence: 99%